2008
DOI: 10.1093/ajcn/87.5.1290
|View full text |Cite
|
Sign up to set email alerts
|

Food selection based on total antioxidant capacity can modify antioxidant intake, systemic inflammation, and liver function without altering markers of oxidative stress

Abstract: Selecting foods according to their TAC markedly affects antioxidant intake and modulates hepatic contribution to systemic inflammation without affecting traditional markers of antioxidant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 50 publications
8
102
2
6
Order By: Relevance
“…Valtueña et al (2008) found that the total antioxidant capacity of food correlated with the liver function whereas plasma total antioxidant capacity did not change. Hepatic inflammation seems to contribute to the low-grade systemic inflammation associated with the metabolic syndrome (Valtueña et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Valtueña et al (2008) found that the total antioxidant capacity of food correlated with the liver function whereas plasma total antioxidant capacity did not change. Hepatic inflammation seems to contribute to the low-grade systemic inflammation associated with the metabolic syndrome (Valtueña et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Valtueña et al (2008) found that the total antioxidant capacity of food correlated with the liver function whereas plasma total antioxidant capacity did not change. Hepatic inflammation seems to contribute to the low-grade systemic inflammation associated with the metabolic syndrome (Valtueña et al, 2008). In our study, the plasma antioxidant capacity measured as ORAC did not change statistically significantly in either group, although there was an increasing trend, and the trend was stronger in the berry group.…”
Section: Discussionmentioning
confidence: 92%
“…Nutrient data for specific foods were obtained from the food composition database for epidemiological studies in Italy (Salvini et al, 1998) integrated with the TAC values of a number of foods representative of the average Italian diet, such as fruits, vegetables, oils, beverages, spices, dried fruits, sweets, cereals, pulses and nuts (Pellegrini et al, 2003(Pellegrini et al, , 2006. The TAC database has been widely validated in the Italian population (Brighenti et al, 2005;Valtueña et al, 2008;Del Rio et al, 2011) as well in Spanish (Agudo et al, 2007) and Greek populations (Detopoulou et al, 2010;Psaltopoulou et al, 2011).…”
Section: Study Subjectsmentioning
confidence: 99%
“…A total of 34 healthy adults were recruited among a population of workers and former workers of a food company in the Parma area, as described elsewhere (Valtueña et al, 2008). Exclusion criteria were diabetes mellitus, cardiovascular events, evidence of hepatitis B virus or hepatitis C virus infection, chronic liver diseases or nephropathies, cancer, organ failure, smoking, last menses within the past 12 months, taking cholesterol-lowering or antiinflammatory medications, and having taken hormone replacement therapy for the past 12 months.…”
Section: Participantsmentioning
confidence: 99%
“…The study was originally designed with the primary objective of investigating the effects of low and high-antioxidant diets on systemic inflammation and liver dysfunction, as previously reported (Valtueña et al, 2008), and also to assess whether dietary TAC could influence plasma concentrations of b-carotene while controlling for other dietary factors known to affect b-carotene concentrations, including its own intake. Briefly, participants were asked to follow a high-TAC diet (HT) and a low-TAC diet (LT) for 14 days each, with a 14-day washout period (WO) in between.…”
Section: Study Design and Sample Collectionmentioning
confidence: 99%